DROUGHT RESISTANT SELECTION ON SOYBEAN SOMACLONAL VARIANTS - Widoretno, Wahyu; Arumingtyas, Estri Laras; Basuki, Nur; Soegianto, Andy (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
This research was conducted to evaluate the yield potential of 19 somaclonal variants resulting from in vitro selection when planted under drought stress condition in the field. Field test was done by planting the variants, the parents, and checked varieties in the field during dry season, and was irrigated once a week for non-stress and once two weeks for drought stress treatment. Split-plot design arranged in a factorial (2 x 28) with three replications was used in this research. Observations were done on yield and yield components. Analysis of variance was used to see the difference between treatments and then it was continued with analysis using Honestly Significant Difference test to find out the best treatments. There was no interaction between genotype and drought stress on seed yield. Different genotypes showed a significant difference on this character. It indicated that the yield potential of selected variants was not affected by drought stress treatment. This research gave 10 variants having the potential to be developed as drought resistant genotypes. However, these ten potential genotypes need to be tested further in field trial to find out the yield adaptability and stability and their resistance to drought stress. Â Keywords: somaclonal variants, in vitro selection, drought stress, soybean, selection